Tourist boom in Iceland – the challenges of sustainable development - Bołdak, Agnieszka; Stefanowska, Agata; Niwiński, Michał (Studia Ecologiae et Bioethicae, 2018)
Iceland as an exceptional island, both in terms of natural and cultural values, creates perfect conditions for practicing various forms of tourism and recreation, focused on contact with nature. At present, tourism has become one of the the dominant branches of the country’s economy. The rapid development of tourism causes a proportional increase in impact on Iceland’s natural resources. In relation to the size of the island and its position [location] in the Arctic, even a small tourist traffic causes changes in the environment. The Icelandic authorities recognize the challenges they face in the context of the further development of the tourism industry and undertake activities aimed at the sustainable development of this area. The purpose of this article is to analyze the impact of Iceland’s tourist development on the natural values of the island in the light of the idea of sustainable development. Iceland as an exceptional island, both in terms of natural and cultural values, creates perfect conditions for practicing various forms of tourism and recreation, focused on contact with nature. At present, tourism has become one of the the dominant branches of the country’s economy. The rapid development of tourism causes a proportional increase in impact on Iceland’s natural resources. In relation to the size of the island and its position [location] in the Arctic, even a small tourist traffic causes changes in the environment. The Icelandic authorities recognize the challenges they face in the context of the further development of the tourism industry and undertake activities aimed at the sustainable development of this area. The purpose of this article is to analyze the impact of Iceland’s tourist development on the natural values of the island in the light of the idea of sustainable development. Islandia jako wyspa wyjątkowa zarówno pod względem walorów przyrodniczych jak i kulturowych, stwarza doskonałe warunki do uprawiania różnych form turystyki i rekreacji nastawionych na kontakt z naturą. Obecnie ...